Strategi Dakwah Dalam Membina Akhlak Remaja di Desa Bendung Air Kayu Aro - Ahmad Zuhdi; Ahmad Khairul Nuzuli; Febrianto Febrianto (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2022)
The progress of the times and technology makes young adolescents absorb values from anywhere, including negative values. This has a serious impact on adolescent morals. This study wanted to see how the right da'wah strategy in fostering adolescent morals in the village of Bendung Air Kayu Aro. This research method is descriptive qualitative. Data collection is done by interview process. The results of the study show that there is success in communicating messages of moral values. This shows that the emotional, intellectual, and sensory tactics and principles used have brought positive changes to adolescents, as evidenced by the increase in the quality of adolescent worship and the increase in adolescent morale.